2019
DOI: 10.7717/peerj.7574
|View full text |Cite
|
Sign up to set email alerts
|

Plant density and life history traits of Aconitum spicatum in North-central Nepal: effects of elevation and anthropogenic disturbances

Abstract: Increasing cross-border trade of medicinal and aromatic plants (MAPs) has put heavy pressure on a considerable number of species in the Himalayas. One of the threatened species in Nepal is Aconitum spicatum. Unfortunately for this species and for many others, our knowledge on population ecology and performance across the distribution range is insufficient, hindering the formulation of species-specific management plans. We therefore studied density and population structure of A. spicatum and assessed variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…We established the temporary plots using the methods described by Chapagain et al (2019). At each site, we identified three populations of D. hatagirea along an elevation gradient ranging from 3,400 to 3,900 m along the Upper Chamelia valley of ANCA and 3,400-4,600 m along the Gyasumdo valley in Manang (Figure 1, Table S1: Appendix S1).…”
Section: Sampling Design Used In the Vegetation Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…We established the temporary plots using the methods described by Chapagain et al (2019). At each site, we identified three populations of D. hatagirea along an elevation gradient ranging from 3,400 to 3,900 m along the Upper Chamelia valley of ANCA and 3,400-4,600 m along the Gyasumdo valley in Manang (Figure 1, Table S1: Appendix S1).…”
Section: Sampling Design Used In the Vegetation Surveymentioning
confidence: 99%
“…Environmental conditions and interactions associated with altitude play a significant role in the composition and distribution of orchid populations Djordjević et al, 2016Jacquemyn et al, 2005). Alpine and subalpine grasslands suffer from reduced nutrient availability and harsh environmental conditions, and plants growing in these habitats presumably develop adaptive coping strategies (Chapagain et al, 2019). Disturbance regimes, such as harvesting, grazing, trampling, and fire, also play influential positive (Chen et al, 2014;Dai et al, 2019) or negative (Chapagain et al, 2019;Kreziou et al, 2015) roles in determining the growth and persistence of plants and could be important elements of an optimal grassland management strategy for alpine meadows.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In such situations where younger generation is reluctant to peruse traditional practices, preservation of traditional knowledge and effective methods for knowledge transfer within the society, along with resource protection, become essential. Medicinal and aromatic plants growing at higher elevations are sensitive to harvest (Chapagain et al 2019(Chapagain et al , 2020Ghimire et al 2008b;Poudeyal et al 2019), and overharvesting poses a significant threat to the population of many such species in Nepal (Chapagain et al 2021, Ghimire & Nepal 2007, Ghimire et al 2005. In Khumbu Valley, harvesting of very small amount of Neopicrorhiza strictly for local use probably may not pose great threat.…”
Section: Harvesting Period/stage % Of Total Age-wise Respondentsmentioning
confidence: 99%
“…The elevation is frequently reported as one of the key factors, affecting the distribution of plant taxa, especial endemic, in different mountain regions (Vetaas & Grytnes, 2002;Wang et al, 2003;Singh et al, 2007;Subedi et al, 2015), including Carpathian Mountains (Tsaryk et al, 2003;Piękoś-Mirkowa & Mirek, 2009;Kyyak et al, 2016;Mráz et al, 2016). In particular, elevation has confirmed influence on the origination of genetic diversity and speciation in mountain plants (Thiel-Egenter et al, 2009), including Aconitum representatives (Hardin, 1964;Sutkowska et al, 2013;Chapagain et al, 2019). In our preliminary investigations, we have also suggested that elevation may be the factor determining the structure of the inflorescence in A. variegatum L. (Novikoff, 2009).…”
Section: Species Distribution Modelingmentioning
confidence: 99%